Pemanfaatan Telehealth pada Lansia dengan PPOK - Anyta Hera Wahyuni; Rr. Tutik Sri Hariyati (Journal of Telenursing (JOTING), 2023)
This study aims to provide remote health services through monitoring and consultation. Research method with literature review on PubMed, Elsevier, and ProQuest databases. Study design regarding telehealth in geriatric patients with COPD. Elderly participants aged 50 years and over with a diagnosis of COPD. The results showed that elderly patients can accept telehealth because it makes it easier to get health services and improves their quality of life. In conclusion, telehealth is concerned with the patient's ability to understand the health information the health facility needs. Keywords: Geriatrics, Elderly, COPD, Telehealth